Efecto de la presencia de antioxidantes en el diluyente de refrigeración sobre la calidad seminal y la oxidación lipídica del plasma seminal en conejo - López-Mendoza, Yolvi (2018)
Storage of rabbit semen for longer than 36 h causes deterioration of semen quality. Therefore, the aim of this study was to evaluate the addition of antioxidants, membrane protective and/or aminopeptidase activity substances to an EDTA supplemented extender on rabbit semen quality preserved at 16ºC during 72 h. Experiment one was carried out to evaluate the effect of the inclusion of two water soluble analogs of vitamin E (Trolox and ¿-tocopherol) and / or dextran on spermatozoa motility, viability, acrosome status and membrane functionality. In a second experiment the inclusion of bestatin in the extenders with Trolox and / or dextran on seminal quality and lipid oxidation was evaluated. The presence of ¿-tocopherol in the extender significantly decreased all seminal quality parameters over time, whereas the presence of Trolox and dextran did not affect them. In the second experiment, no significant differences among the experimental extenders were observed either for the seminal quality parameters or for the lipid oxidation of the seminal plasma at 72 hours of refrigeration. The cooling time significantly affected the viability and integrity of the acrosome (P <0.05), however, no significant differences were observed in the kinetic parameters, membrane functionality and lipid oxidation of the seminal plasma, showing at 72 and 0 hours similar values. The inclusion of bestatin in all extenders had a positive effect on semen conservation, maintaining the semen characteristics and lipid oxidation over time, regardless of whether the extender was supplemented or not with dextran or Trolox. In conclusion, the combination of EDTA and bestatin proved to be a suitable alternative in the refrigerated semen extender since it avoids the antioxidant activity and maintains membrane motility and functionality over the cooling period studied.